Inorganic biomaterials‐based bioinks for three‐dimensional bioprinting of regenerative scaffolds. Issue 4 (15th March 2022) - Qin, Chen; Wu, Chengtie
Abstract: The application of inorganic biomaterials in regenerative medicine is increasingly expanded. Taking advantages of attractive properties of the inorganic biomaterials, sorts of functional bioinks have been developed based on inorganic biomaterials and were applied to construct inorganic/organic/cell‐laden systems for tissue regeneration via 3D bioprinting technology. In this review, we aim to summarize the existing inorganic biomaterials‐based bioinks (referred to as "inorganic‐bioinks") for 3D bioprinting regenerative scaffolds. We introduce the recently developed inorganic‐bioinks from the perspective of the function of bioinks, and especially highlight the incorporation of inorganic biomaterials improving the printability, mechanical strength, and bioactivity of the bioinks for different tissue regeneration. Subsequently, the current applications of the inorganic‐bioinks in constructing 3D cell‐laden scaffolds for tissue regeneration are presented. Finally, challenges and prospects for the inorganic biomaterials‐based bioprinting strategy are discussed. Abstract : Taking advantages of attractive properties of the inorganic biomaterials, sorts of functional bioinks have been developed based on inorganic biomaterials and were applied to construct inorganic/organic/cell‐laden systems for tissue regeneration via 3D bioprinting technology. In this review, the authors aim to summarize the existing inorganic biomaterials‐based bioinks (referred to as "inorganic‐bioinks") for 3D bioprinting regenerative scaffolds.